THE HEALING POWER OF MUSIC. MUSIC IN PRACTICE - Szilvia TÖRÖK (Studia Universitatis Babeş-Bolyai. Musica)
Feelings, emotions – musical ones too – are constituted by the simplest elements, which form the basis of psychological phenomena. Their knowledge is indispensable in order to be able to approach the psychology of hearing, of sound and music psychology. The brain research conducted in the second half of the 20th century has demonstrated the fact that the right hemisphere is the one responsible for music: it has the functions of recognizing melody, while the left one to identify rhythm. Music has a particular effect on the aesthetic functions of emotions, polishing, educating and - if need be – healing them. The most important role of music, however, is preventing the possible ailments of our emotional world.